Ответ:
a) 6x⁴ + 15x² - 9 = 0
x² = t
6t² + 15t - 9 = 0
t = -3
t = 1/2
x² = -3
x² = 1/2
x = -
/2
x =
/2
Ответ: x₁ = -
/2
x₂ =
/2
б) 2(x+3)⁴ - 5(x+3)² - 3 = 0
t = (x+3)²
2t² - 5t - 3 = 0
t = -1/2
t = 3
(x+3)² = -1/2
(x+3)² = 3
x = -
-3
x =
-3
Ответ: x₁ = -
-3; x₂ =
-3
в) 12/(x-1) - 8/(x+1) = 2
12/(x-1) - 8/(x+1) = 2, x≠1, x≠-1
12/(x-1) - 8/(x+1) - 2 = 0
![\frac{12(x+1) - 8(x-1) - 2(x-1)(x+1)}{(x-1)(x+1)} = 0 \frac{12(x+1) - 8(x-1) - 2(x-1)(x+1)}{(x-1)(x+1)} = 0](https://tex.z-dn.net/?f=%5Cfrac%7B12%28x%2B1%29%20-%208%28x-1%29%20-%202%28x-1%29%28x%2B1%29%7D%7B%28x-1%29%28x%2B1%29%7D%20%3D%200)
![\frac{12x+12 - 8x + 8 - 2(x^2 - 1)}{(x-1)(x+1)} = 0 \frac{12x+12 - 8x + 8 - 2(x^2 - 1)}{(x-1)(x+1)} = 0](https://tex.z-dn.net/?f=%5Cfrac%7B12x%2B12%20-%208x%20%2B%208%20-%202%28x%5E2%20-%201%29%7D%7B%28x-1%29%28x%2B1%29%7D%20%3D%200)
![\frac{12x + 12 - 8x + 8 - 2 x^2 + 2}{(x-1)(x+1)} = 0 \frac{12x + 12 - 8x + 8 - 2 x^2 + 2}{(x-1)(x+1)} = 0](https://tex.z-dn.net/?f=%5Cfrac%7B12x%20%2B%2012%20-%208x%20%2B%208%20-%202%20x%5E2%20%2B%202%7D%7B%28x-1%29%28x%2B1%29%7D%20%3D%200)
![\frac{4x + 22 - 2 x^2}{(x-1)(x+1)} = 0 \frac{4x + 22 - 2 x^2}{(x-1)(x+1)} = 0](https://tex.z-dn.net/?f=%5Cfrac%7B4x%20%2B%2022%20-%202%20x%5E2%7D%7B%28x-1%29%28x%2B1%29%7D%20%20%3D%200)
4x + 22 - 2x² = 0
-2x² + 4x + 22 = 0
x² + 4x + 22 = 0
x = ![\frac{-(-2) +- sqrt((-2)^2 - 4 * 1*(-11))}{2*1} \frac{-(-2) +- sqrt((-2)^2 - 4 * 1*(-11))}{2*1}](https://tex.z-dn.net/?f=%5Cfrac%7B-%28-2%29%20%2B-%20sqrt%28%28-2%29%5E2%20-%204%20%2A%201%2A%28-11%29%29%7D%7B2%2A1%7D)
x = (2±
)/2
x₁ = (2+ 4
)/2
x₂ = (2- 4
)/2
Ответ: x₁ = 1-2
; x₂ = 1 +2